POSSIBILITIES OF TRANSFUSION THERAPY IN SURGICAL PRACTICE - I. G. Dutkevich; A. V. Koloskov (Вестник хирургии имени И.И. Грекова)
The up-to-date possibilities of transfusion therapy are presented in the article. The authors analyzed their own experience and made a review of literature. The study considers the mechanisms of treatment, immunological and infectious risks, indications and contraindications for application of transfusion therapy in surgical practice.